Gambaran Resiliensi pada Ibu dengan Anak Speech delay - Assila Corina Lahallo; Fatchiah E. Kertamuda (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Children experiencing Speech delay, also known as delayed speech, have special needs. Therefore, Speech delay poses its own challenges for mothers. Thus, the role of parents considered most significant in child development is that of the mother, who must demonstrate resilience in facing the situation of a child with Speech delay. This study aims to provide an overview of Resilience in Mothers with Children with Speech delay. The research employed a qualitative method. The subject in this study was a 33 years old mother with a speeh delay child, the child had been diagnosed for more than 1 year, and the child had or was in the process of therapy. Primary data were obtained from the words or interview results from mothers with children with speech disorders. Analysis was conducted using techniques such as those proposed by Miles and Huberman, namely Reduction, Presentation, and Conclusion drawing.